2016
DOI: 10.1155/2016/7074829
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Effector/Regulatory Cells Characterization in the Physiopathology of Cutaneous Lupus Erythematous: A Cross-Sectional Study

Abstract: We compared the presence of diverse cytokines and regulatory T and B cells in skin biopsies of discoid lupus erythematosus (DLE) and subacute cutaneous lupus erythematosus (SCLE). We included 19 patients with DLE, 13 with SCLE, 8 healthy controls, and 5 patients with hypertrophic scars. We assessed the CLASI activity score. To determine IL-22-producing cells and the subpopulation of CD4+/IL-17A+-, CD4+/IL-4+-, and CD4+/IFN-γ +-expressing T cells, CD123+/IDO+ pDCs, CD25+/Foxp3+ Tregs, and CD20+/IL-10+-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
(45 reference statements)
0
29
0
1
Order By: Relevance
“…It indicates its potential as markers of the amount and extent of periodontal damage in patients with SLE. The dermis and epidermis from tissues of patients with SLE had significantly higher percentage of IL‐4 + /CD4 + T cells compared to healthy donor groups . The above research indicates that IL‐4 plays a significant role in local lesion tissue in SLE, although at insignificant serum levels.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 71%
See 1 more Smart Citation
“…It indicates its potential as markers of the amount and extent of periodontal damage in patients with SLE. The dermis and epidermis from tissues of patients with SLE had significantly higher percentage of IL‐4 + /CD4 + T cells compared to healthy donor groups . The above research indicates that IL‐4 plays a significant role in local lesion tissue in SLE, although at insignificant serum levels.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 71%
“…The dermis and epidermis from tissues of patients with SLE had significantly higher percentage of IL-4 + /CD4 + T cells compared to healthy donor groups. 44 The above research indicates that IL-4 plays a significant role in local lesion tissue in SLE, although at insignificant serum levels. Most studies have focused on the B-cell stimulatory properties of IL-4 in the development of autoantibody production.…”
Section: Sys Temi C Lupus Ery Thematosusmentioning
confidence: 81%
“…A significant understanding of the cellular infiltrate found in psoriasis lesions exists in that there are elevated levels of IL‐17A and IL‐22; however, in DLE lesions, one study has found low levels of these cytokines and only IFN‐ γ producing CD4 + T cells . Notably, other studies have produced contrasting data in which IFN‐ γ , IL‐17A, and IL‐22 producing CD4 + T cells are all elevated in DLE skin lesions; this contrast reflects the complexity and broad nature of immunological involvement in this cutaneous condition . Although this discrepancy exists, there is still evidence of unique aspects of DLE pathophysiology with respect to targeting IFN‐ γ and the Th1 cell inflammatory immune response.…”
Section: Discoid Lupus Erythematosus Pathophysiologymentioning
confidence: 99%
“…Specific analysis of DLE lesions has been conducted to determine the molecular transcriptome of DLE; the transcription and expression of certain genes; and involvement of immunological signal transduction pathways . Furthermore, some studies have compared the histology of DLE lesions with those of psoriasis.…”
Section: Discoid Lupus Erythematosus Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation